(untitled) (Journal of the Spanish Institute for Strategic Studies, 2020)
The key objective in the public relations strategy of any military organization is the generation of trust among its publics. For this, the attention and continuous improvement of its reputation is essential. The digital medium, in which organizations are subject to continuous scrutiny and which demands immediacy, success and coherence, has a great influence, also, on the offline world. Therefore, digital reputation becomes a strategic issue in relations with all its publics. In the Reputation Age, the use of digital reputation as a public relations strategy in military organizations is a necessary and essential process in the current environment that has long-term effects and that must be planned. It has transformative effects in the talent of the organization that imply desired changes in the corporate culture and, consequently, adapt the organization to the demands of today’s digital society.